Evaluasi Kemampuan Kesuburan Tanah di Kecamatan Tutur Pasuruan - Arief A.M; Bakti Wisnu W; Wanti Midarti (Universitas Islam Malang, 2022)
The aim of this study was to discover soil fertility indicators for coffee cultivation in Tutur District as well as the variables that influence soil fertility levels for coffee cultivation land. A survey method was employed in this investigation. The findings of the chemical characteristics test were utilized as a guide for creating maps of the land fertility potential for coffee plants in Tutur Village. These maps included information on water content, soil pH, C-Organic content, N-total content, Phosphorus content, base saturation, and CEC. According to this study, Tutur District's coffee farming may be classified into three soil fertility status categories: low, medium, and high fertility status. The slope of the land is the factor that has the biggest impact on the soil fertility in the Tutur District's coffee growing region; the steeper the slope, the less fertile the soil is.